2010
DOI: 10.1080/02640414.2010.521166
|View full text |Cite
|
Sign up to set email alerts
|

Sprinting analysis of elite soccer players during European Champions League and UEFA Cup matches

Abstract: It has been suggested that assessment of high-intensity activities during a match is a valid measure of physical performance in elite soccer. Recently, sprinting activities have been analysed in more depth. The aim of this study was to develop a detailed analysis of the sprinting activities of different playing positions during European Champions League and UEFA Cup competitions. Altogether, 717 elite outfield soccer players were evaluated throughout 2002-2006 using ProZone® (Leeds, UK). Sprinting (explosive a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
202
4
28

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 254 publications
(249 citation statements)
references
References 16 publications
15
202
4
28
Order By: Relevance
“…These technologies are more time efficient than the traditional video-based time motion analysis systems and offer greater objectivity and volume of information [4]. Furthermore, more detailed evaluations of specific elements of a player's physical performance as opposed to generic time-motion analysis can be undertaken [5][6][7][8]. Despite advancements in the understanding of match-play in elite male players, published research on elite female players is lacking [9], predominantly due to stadium access and financial considerations.…”
mentioning
confidence: 99%
“…These technologies are more time efficient than the traditional video-based time motion analysis systems and offer greater objectivity and volume of information [4]. Furthermore, more detailed evaluations of specific elements of a player's physical performance as opposed to generic time-motion analysis can be undertaken [5][6][7][8]. Despite advancements in the understanding of match-play in elite male players, published research on elite female players is lacking [9], predominantly due to stadium access and financial considerations.…”
mentioning
confidence: 99%
“…Gaelic football, like other field sports such as Australian football (15,16) , rugby league (5,6,7,20,29) and soccer (10,17) has a degree of positional differentiation regarding running performance profiles. Keane et al (28) previouly reported that the midfield positions covered the greatest distances during match play.…”
Section: A C C E P T E Dmentioning
confidence: 99%
“…there is also a proposal to use an individualized velocity threshold for each athlete [16]. On the other hand, Di Salvo et al [10] suggested analysing sprint activities in a more specific way, classifying them as 'explosive' and 'leading' sprint. the authors assessed separately the sprints in which, before reaching the threshold, the athletes were in low velocities (labelled 'explosive sprint') or in moderate velocities ('leading sprint').…”
Section: Introductionmentioning
confidence: 99%
“…However, according to Carling et al [13], there is no agreement on what velocity thresholds should be used in soccer to state that the player is sprinting. For example, thresholds have been reported at velocities of > 8.33 m/s [3], > 7 m/s [10], > 6.39 m/s [1,2], and > 5.83 m/s [9]. there is also a proposal to use an individualized velocity threshold for each athlete [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation